Role of physical activity and metabolic syndrome in determining the risk of postmenopausal breast cancer: a systematic review - Thamil Manni, Shuwaathi; Noris, Calvin Preetivan; Mathialagan, Amuthaganesh; Karisnan, Kanakeswary (International Journal Of Community Medicine And Public Health, 2021)
Physical activity (PA) and metabolic syndrome (MetS) have emerged as crucial factors in facilitating the incidence of postmenopausal (PM) breast cancer (BC). The association of PA, MetS and its components with PM BC was explored in this study. PRISMA guideline was followed and online databases were searched comprehensively to find relevant cohort and case-control studies until 18 February 2021 using keywords such as “physical activity”, “metabolic syndrome” and “breast cancer”. Eligible studies evaluating BC in postmenopausal women with a clear definition and measure of PA, MetS and its individual components were selected. A total of twenty-three articles related to PA and fifteen articles for MetS met the eligibility criteria and were assessed thoroughly. PA and MetS were significantly associated with PM BC. There was evidence of dose-response effect of PA and Mets on PM BC. Obesity, diabetes and dyslipidaemia were independently associated with PM BC and posed an increased risk on PM BC whereas the association of HPTN with PM BC was not prominent. Consistent and sustained long term PA throughout one’s lifetime was observed to decrease PM BC risk whereas increasing number of MetS components increased the risk of PM BC. Routine screening for PM women with ≥2 MetS components and obese or overweight women with any of the MetS components may be beneficial in early BC detection. Lifestyle modifications with emphasis on long term PA would be beneficial to public health in preventing and improving MetS outcomes as well as a primary prevention of sporadic PM BC.